Structure-function mapping of BbCRASP-1, the key complement factor H and FHL-1 binding protein of Borrelia burgdorferi. - Cordes, F; Kraiczy, P; Roversi, P; Simon, M; Brade, V; Jahraus, O; Wallis, R; Goodstadt, L; Ponting, C; Skerka, C; Zipfel, P; Wallich, R; et al. (2006)
Borrelia burgdorferi, a spirochaete transmitted to human hosts during feeding of infected Ixodes ticks, is the causative agent of Lyme disease, the most frequent vector-borne disease in Eurasia and North America. Sporadically Lyme disease develops into a chronic, multisystemic disorder. Serum-resistant B. burgdorferi strains bind complement factor H (FH) and FH-like protein 1 (FHL-1) on the spirochaete surface. This binding is dependent on the expression of proteins termed complement-regulator acquiring surface proteins (CRASPs). The atomic structure of BbCRASP-1, the key FHL-1/FH-binding protein of B. burgdorferi, has recently been determined. Our analysis indicates that its protein topology apparently evolved to provide a high affinity interaction site for FH/FHL-1 and leads to an atomic-level hypothesis for the functioning of BbCRASP-1. This work demonstrates that pathogens interact with complement regulators in ways that are distinct from the mechanisms used by the host and are thus obvious targets for drug design.